Little Beaver and The Echo - MacDonald, Amy (New York, NY : Putnam Berkley Group, Inc, 1990)
Unaware that the voice from across the pond telling him he's lonely is his echo, a little beaver sets out to make a friend of that voice, encountering real animal friends on the way.
Keywords: Friendship -- Fiction; Beavers -- Fiction